Differential Market Reaction to Pooling and Purchase Methods. - Davis, Michael L. (The Accounting Review, 1990)
Reexamines the impact of merger accounting method by using a sample of tax-free mergers drawn from a different time period and using more refined cumulative average residual methodology. Nonmerger-related capital asset pricing model; Postmerger indirect cash-flow impacts.